Legal Aspects of Determination of Tax Collection on Land and Building Rights Acquisition in Jayapura Regency - Pelupessy, Eddy (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to examine the implementation of the collection of Land and Building Acquisition Tax in Jayapura Regency. To examine the obstacles that arise in the implementation of the collection of Land and Building Acquisition Tax in Jayapura Regency. The research method is sociological juridical, namely a legal research approach that examines law not only as a formal rule, but also as a social phenomenon that has an influence and is influenced by society. This approach uses qualitative research methods, such as interviews and observations, to understand how the law is applied and how society interacts with the law. The results of this study reveal that the implementation of the collection of Land and Building Acquisition Tax in Jayapura Regency is when there is a transfer of land and building rights due to a sale and purchase with a transaction value lower than the market price, the transaction value will be determined by DPPKAD officers based on the market price and a survey of the relevant taxable object, whereas the provisions of Article 87 paragraph 2 of Law Number 28 of 2009 and Article 7 of Jayapura Regency Regional Regulation Number 2 of 2011 state that the basis for imposing BPHTB tax on the acquisition of sale and purchase rights with a transaction value lower than the market price, then the basis for imposing BPHTB tax is the Taxable Object Sales Value (NJOP) of Land and Building Tax.